An Arabidopsis lipid map reveals differences between tissues and dynamic changes throughout development. (24th May 2021) - Kehelpannala, Cheka; Rupasinghe, Thusitha; Pasha, Asher; Esteban, Eddi; Hennessy, Thomas; Bradley, David; Ebert, Berit; Provart, Nicholas J.; Roessner, Ute
Summary: Mass spectrometry is the predominant analytical tool used in the field of plant lipidomics. However, there are many challenges associated with the mass spectrometric detection and identification of lipids because of the highly complex nature of plant lipids. Studies into lipid biosynthetic pathways, gene functions in lipid metabolism, lipid changes during plant growth and development, and the holistic examination of the role of plant lipids in environmental stress responses are often hindered. Here, we leveraged a robust pipeline that we previously established to extract and analyze lipid profiles of different tissues and developmental stages from the model plant Arabidopsis thaliana . We analyzed seven tissues at several different developmental stages and identified more than 200 lipids from each tissue analyzed. The data were used to create a web‐accessible in silico lipid map that has been integrated into an electronic Fluorescent Pictograph (eFP) browser. This in silico library of Arabidopsis lipids allows the visualization and exploration of the distribution and changes of lipid levels across selected developmental stages. Furthermore, it provides information on the characteristic fragments of lipids and adducts observed in the mass spectrometer and their retention times, which can be used for lipid identification. The Arabidopsis tissue lipid map can be accessed at http://bar.utoronto.ca/efp_arabidopsis_lipid/cgi‐bin/efpWeb.cgi . Significance Statement: With the complexity of plant lipids, a web database collecting information on plant lipids is of great value. Here the most comprehensive and detailed tissue‐specific lipid profile of Arabidopsis thaliana across developmental stages is provided in the form of an open‐source, electronic Fluorescent Pictograph (eFP) browser, along with insights into lipid dynamics across plant growth and development. This resource will significantly advance future research into the Arabidopsis lipidome and facilitate research into other plants.